Pentecostal churches in transition: analysing the developing ecclesiology of the Assemblies of God in Australia - Clifton, Shane (Global Pentecostal and Charismatic studies 1876-2247, 2009)
Preface; Chapter One. Pentecostal Ecclesiology; Chapter Two. From Faith Missions to Churches, 1800s to 1930s; Chapter Three. Formation of a Democratised National Fellowship, 1930s to 1960s; Chapter Four. Growth, Controversy and Revolution, 1960s to present; Chapter Five. Conclusion: Looking Forward and Thinking Globally; Bibliography; Index.